CHILDREN OF TRANSITION IN MODERN UKRAINIAN LITERATURE FOR YOUNG READERS - T. B. , Kachak (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The problem of influence of the transitional epoch of the 1990s on the formation of a young generation is becoming topical in modern Ukrainian literature. This problem is well covered in modern Ukrainian literature for children and youth. Writers (Zirka Menzatyuk, Olena Zaharchenko, Stepan Protsiuk) reveal emotions and experiences of children in the collapse of the Soviet Union, their perception of ideological, cultural and social changes in society. The main characters of stories – children and adolescents, whose outlook, character and approach to life are shaped by the events taking place in the country. This is a different generation – the "free generation" which professes democratic values, an active social position, defending human rights and turns its face to the nation's history, culture and traditions. The stories «How I destroyed the empire» by Zirka Menzatiuk, «Hutir» by Olena Zakharchenko, «Vitrolomy» by Stepan Protsiuk are the mirror in which we see children of the transitionn period in Ukraine.